EFFECT OF PUNARNAVADI KASHAYAM AND ASWAGANDHA CHOORNA IN PREMENSTRUAL SYNDROME - Akhila M; N.Vijayakumar; Kannan VS (International Journal of Ayurveda and Pharma Research, 2020)
Premenstrual syndrome (PMS) is a common disorder of young and middle-aged women characterized by cyclic occurrence in the luteal phase of the menstrual cycle of a combination of distressing physical, psychological and behavioral changes of sufficient severity to result in deterioration of inter- personal relationships; which remit upon onset or immediately after menstruation. PMS is due to doshic imbalance and impairment of satwa. Objective of study is to find out the effect of Punarnavadi kashayam and Aswagandha choornam in Premenstrual syndrome. Study design was interventional, pre and posttest with a sample size of 20. Females of age group 20-35 years with PMS fulfilling the American College of Obstetrics and Gynecology criteria of PMS was selected. Punarnavadi Kashayam in the dose of 48 ml bid, 30 minutes before food and Aswagandha choorna in the dose of 3 gm. bid along with kashaya. Administration of drug started 14 days before menstruation and was continued till fourth day of menstruation for three consecutive cycles. Follow up was done for next two consecutive cycles. Patient was assessed on fifth day of menstruation during study period and follow up period. The research drug had shown effectiveness in the treatment of depressive effect, anxiety, fatigue, irritation, depressive thoughts, pain, appetite changes, sleep changes, bloating assessed by premenstrual scale. Both drugs showed effectiveness in normalizing serum sodium and serum potassium levels. Associated premenstrual complaints also subsided. Study concluded that Punarnavadi kashaya and Aswagandha choorna is very much effective in treating Premenstrual syndrome.